Polyurethanes with aggregation-enhanced emission characteristics: preparation and properties. (5th December 2016) - Wang, Kun; Yang, Jiping; Gong, Chen; Lu, Hao
Abstract : An amino-terminated poly(propylene glycol)-modified tetraaryl-buta-1, 3-diene derivative (TABDAA) was introduced to synthesize polyurethanes with different ratios of soft/hard segments. A mixture of TABDAA and poly(tetrahydrofuran) 1000 as the soft segments was reacted with 4, 4-diphenylmethane diisocyanate and 1, 4-butanediol as the hard segments in molar ratios of 1 : 2 : 1, 2 : 3 : 1, and 3 : 4 : 1 to give the desired polyurethanes named TMPU-211, TMPU-321 and TMPU-431, respectively. The three polyurethanes exhibited different aggregation-enhanced emission (AEE) behaviors because of their different soft/hard segment ratios. The polyurethanes with a higher soft segment content tended to form bigger particles in a DMF/water mixture solution, thus causing a sharper increase in their fluorescence intensity. In addition, the polyurethane films exhibited different fluorescence intensities after different heat treatments. After a quenching treatment of the soft segments in the polyurethane films, the fluorescence intensity dropped greatly. When these quenched polyurethane films were thermally annealed at 60 °C for 24 hours, their fluorescence intensity exceeded the initial intensity of the as-prepared films. Differential scanning calorimetry results showed that the polyurethane films in the quenched condition did not present the endothermal melting peak of the soft segments, and the melting peaks appeared again after thermal annealing. AFM experiments showed that an ordered arrangement was achieved after the heat treatment of these AEE polyurethane films. These results demonstrated that the polymer structure had a significant effect on the AEE properties of the polyurethane films, and more importantly, it is of great significance in improving the fluorescence emission of the AEE polymers and also for their potential application in fluorescent probes, stimuli-responsive materials, PLED devices and so on.